Exploring the relationship between dietary quality, eating behavior, and mental health among young adults - Poslt Königová, Michaela; Sebalo Vňuková, Martina; Sebalo, Ivan; Koleničová, Veronika; Urbanová, Lucie; Řehořková, Petra; Anders, Martin (Frontiers in Nutrition, 2025)
BackgroundNutritional psychiatry has established that nutrient-dense diets rich in fruits, vegetables, whole grains, and lean proteins are associated with lower rates of depression and anxiety, while diets high in refined sugars and saturated fats predict greater psychological distress. Although emotion-regulation strategies are known to influence eating behavior, evidence on their role in shaping overall diet quality remains scarce, particularly in Central and Eastern European populations. Young adulthood (18–30 years) represents a critical developmental stage in which both mental health vulnerabilities and long-term dietary patterns consolidate, yet no prior study has examined how discrete cognitive emotion-regulation strategies relate to both global diet quality and specific eating behaviors in Czech young adults.MethodsIn the Czech Republic, we conducted a cross-sectional survey of 1,027 young adults (507 men, 520 women; mean age = 24.6, SD = 3.3 years) recruited via quota-based convenience sampling matched to the 2021 census on age (18–30 years), sex, education, and region. Data were collected in three 60-min online sessions. Participants completed validated Czech measures of depression (BDI), anxiety (BAI), psychological distress (SCL-90), burnout (Shirom-Melamed Burnout Measure), and nine CERQ subscales—all demonstrating α ≥ 0.89 in prior validations and α ≥ 0.79 in our pilot (N = 50). Diet quality was assessed using a 30-item Czech FFQ (pilot α = 0.81), from which Diet Quality Index International (DQI-I) scores were computed. Eating behaviors were measured with the 31-item Czech Adult Eating Behavior Questionnaire (AEBQ; α_total = 0.79). We used stepwise multiple regression with all variance inflation factors < 2.0 to identify psychological variables associated with DQI-I and with “food-approach” versus “food-avoidance” behaviors, minimizing overfitting.ResultsIn exploratory stepwise regression models (all variance inflation factors < 2.0), the DQI-I model explained a small proportion of variance (Adj R2 = 0.024; f2 = 0.025). Within this model, higher rumination was positively associated with diet quality (B = 0.34, p < 0.001), while depressive symptoms were inversely associated with diet quality (B = −0.09, p = 0.001). The AEBQ model accounted for a modest but meaningful share of variance (Adj R2 = 0.155; f2 = 0.183). In this model, anxiety, catastrophizing, and “focus on the positive” were positively associated with food-approach behaviors (all p < 0.001), whereas positive reappraisal and acceptance negatively associated with dysregulated eating (p < 0.01). These associations should be regarded as tentative and hypothesis-generating, given the exploratory design and modest variance explained.ConclusionThis study is the first census-matched study of Czech young adults to examine emotion-regulation strategies in relation to both diet quality and eating behaviors. These findings reveal complex and partly counterintuitive associations—for example, rumination was linked to healthier diet quality, while some ostensibly adaptive strategies coincided with more dysregulated eating. These results should be interpreted as exploratory and hypothesis-generating, underscoring the potential relevance of cognitive-emotional mechanisms for future nutritional psychiatry interventions. Integrating approaches that address maladaptive strategies such as catastrophizing with dietary guidance may represent a promising direction for prevention and health-promotion efforts but requires confirmation in longitudinal and experimental studies.